Aptamer engineering exosomes loaded on biomimetic periosteum to promote angiogenesis and bone regeneration by targeting injured nerves via JNK3 MAPK pathway. (December 2022) - Su, Yanlin; Gao, Qing; Deng, Rongli; Zeng, Lian; Guo, Jingyi; Ye, Bing; Yu, Jialin; Guo, Xiaodong
Abstract: Repairing critical bone defects is a complex problem in the clinic. The periosteum rich in nerve plays a vital role in initiating and regulating bone regeneration. However, current studies have paid little attention to repairing nerves in the periosteum to promote bone regeneration. Thus, it is essential to construct bionic periosteum with the targeted injured nerves in the periosteum. We coupled phosphatidylserine (PS) targeted aptamers with repair Schwann cell exosomes to construct exosome@aptamer (EA). Then through PEI, EA was successfully built on the surface of the electrospun fiber, which was PCL@PEI@exosome@aptamer (PPEA). Through SEM, TEM, and other technologies, PPEA was characterized. Experiments prove in vivo and in vitro that it has an excellent repair effect on damaged nerves and regeneration of vascular and bones. In vivo, we confirmed that biomimetic periosteum has an apparent ability to promote nerve and bone regeneration by using Microcomputer tomography, hematoxylin-eosin, Masson, and Immunofluorescence. In vitro, we used Immunofluorescence, Real-Time Quantitative PCR, Alkaline phosphatase staining, and other tests to confirm that it has central nerve, blood vessel, and bone regeneration ability. The PPEA biomimetic periosteum has apparent neurogenic, angiogenic, and osteogenic effects. The PPEA biomimetic periosteum will provide a promising method for treating bone defects. Graphical abstract: Image 1 Highlights: To construct a biomimetic periosteum that can target injured axons and bone regeneration. PS targeted aptamer is coupled with repair Schwann cell exosomes. PEI self-assembly was used for the PCL electrospun biomimetic membrane loading. It targeted and repaired the injured axons and promoted the secretion of CGRP and SP. Biomimetic periosteum promotes vascular regeneration and bone regeneration.